Reviews - Susi Peacock; Philip Barker; Clive Betts; Eleri Jones; Sue Fowell (Association for Learning Technology, 2000)
Training in information technology (IT) is becoming a crucial activity for virtually all organizations - a well-worn cliche. Sadly, however, it is all too often the case that training budgets are manipulated and absorbed into other 'worthy' causes. The result is that IT training is hastily passed onto junior members of a team or to postgraduate students who have had little formal training and experience of IT training. It is for these novice trainers that the '500 computer tips' will be particularly useful but it is also a highly worthwhile, accessible reference for more experienced trainers in both academic and non-academic environments. This book (one of a series of '500 Tips' from Kogan Page) does not aim to give technical information about any particular software package but provides readable, understandable generic tips which have a sound pedagogical base (although this is carefully hidden).